Analisis Faktor-Faktor Yang Mempengaruhi Minat Beli Konsumen Pada Produk Air Minum Dalam Kemasan Merek Tir-Sa (Studi Pada PT. Tirta Sari Cemerlang) - Endah Pujiastuti; Iip Dyah Kusumaningati; Putri Seprina (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to determine the effect of product, price, promotion and distribution on consumer buying interest in drinking water products in the brand of tir-sa at PT. Tirta Sari Cemerlang. The method used in this study is a quantitative method. Determination of the sample using simple random sampling technique and the number of samples as many 92 respondents. Data collection techniques using observation, interviews, literature study and questionnaires. While the data analysis techniques used are validity, reliability test, classical assumption test, multiple linear regression test and hypothesis testing. Based on the results of the study, it shows that price and distribution partially have no significant effect on consumer buying interest as evidenced by the t-count value of the price of -0.339 < t table 1.989 with a significant value of 0.736 > 0.05, and the t-count value of the distribution of 0.070 < t table 1.989 with a significant value of 0.994 > 0.05. While products and promotions partially have a significant effect on consumer buying interest as evidenced by the t-count value of the product of 2.401 > t table 1.989 with a significant value of 0.019 < 0.05, and the t-count value of promotion of 3.414 > t table 1.989 with a significance value 0.001 < 0.05. However, simultaneously product, price, promotion and distribution variables have a significant effect on consumer buying interest with a calculated f value of 6.541 > f table 2.48 and a significant value of 0.000 < 0.05.